An unusual case of vulval tuberculosis in pregnancy - Gupta, Neena; Jahan, Uruj; Usmani, Fatima; Rathore, Shweta (Indian Journal of Case Reports, 2019)
Tuberculosis (TB) continued to be a major health problem throughout the world, especially affecting developing countries. India and China together account for 40% of the world’s TB burden. Here, we present a rare case of genital TB in a 24-year-old pregnant woman (G2P1 + 0.34 weeks of pregnancy) with chronic vulval ulcer of 2 years. Histopathological examination was suggestive of TB, but acid-fast bacilli culture of biopsy specimen was found negative. The patient was started on anti-TB therapy. After 3 months, there was a remarkable improvement in her symptoms and >50% regression of the lesion.